(untitled) (Research, Society and Development, 2021)
The effect of organic fertilizers regarding seed quality is still unclear in the literature, as organic insums are already part of the reality of the field and are used by many farmers. In this sense, the objective of this study was to evaluate the physical and physiological quality of girl finger pepper seeds under different doses of organic and mineral fertilizer in Ceres-GO. The experiment was carried out in randomized blocks with the pepper lineage IFET 1572 and six treatments with fertilizer doses: T0 – no fertilizer; T1 – 15 t ha-1 of cattle manure; T2 – 30 t ha-1 of cattle manure; T3 – 45 t ha-1 of cattle manure; T4 – 60 t ha-1 of cattle manure and T5 - mineral fertilizer mineral fertilizer, 334 kg ha-1 of Urea; 277 kg ha-1 of Magnesium Thermophosphate and 144 kg ha-1 of Potassium Chloride. The variables analyzed were: degree of humidity; germination pattern test (TPG); emergency; Electric conductivity; 1000 seed weight and emergence speed index (IVE). Data were subjected to analysis of variance and means compared by Tukey test at 5% probability (p ≤ 0.05). To compare the organic fertilizers, regression was applied. There were significant differences in the physical and physiological quality of the seeds in the emergence, emergence speed index, germination pattern and weight of one thousand seeds under different doses of bovine and mineral manure. Increasing doses of bovine manure negatively interfered with the physical and physiological quality of the seeds from the application of 15 t ha-1. The use of bovine fertilizer can be used for the production of girl finger pepper seeds.